The Origin of the Political State in Aristotle - Ramadan Muhammad Al-Tawfiq (Journal of Scientific and Human Dimensions, 2026)
He identified the primary goal of the state as striving to achieve the common good of citizens by providing a dignified life and realizing justice. He added that good governance is that which contributes to achieving the interests of all members of society, relying on reason and prudent management. Aristotle also emphasizes the importance of the family as the first nucleus from which civil society is formed, which in turn contributes to building the state, as the family is considered the first and fundamental pillar of society. He then addressed different types of governments and believed that the validity of these systems is a relative matter, such that no political system can be described as suitable for all times and places. He considered good governance to be that which achieves the interests of all members of society. Finally, understanding Aristotle’s view of the emergence of the state contributes to enriching philosophical and political debates and enhances our ability to analyze contemporary challenges. Aristotle’s ideas about the state and just governance remain relevant to modern discussions of justice and social responsibility. Therefore, the study of Aristotle remains an important source for understanding the philosophical foundations of politics and governance and opens the way for further studies on the impact of Aristotelian political philosophy on modern thought.